Evaluation of the status of use of chemicals and antibiotics in freshwater aquaculture activities with special emphasis to fish health management - Faruk, MAR; Ali, MM; Patwary, ZP (Journal of the Bangladesh Agricultural University, 2010)
The study was carried out to understand current status of use of chemicals and antibiotics in fish health management in freshwater aquaculture activities. Data were collected through questionnaire interview, personal contact, market survey and participatory rural appraisal like focus group discussion with fish and prawn farmers, retailers of animal medicine and representatives of pharmaceutical companies. A range of chemicals including antibiotics were found available in market. Fish health management and disease treatment were the major areas where majority of such chemicals have been used. Other uses included pond preparation and management, growth promotion and improvement of water quality to enhance pond productivity. Commonly found traditional chemicals in health management included Lime, Salt, Potassium permanganate, Sumithion, Melathion, Formalin, Bleaching powder and Malachite green. Of the new products JVzeolite, Geotox, Green zeolite, Orgavit aqua, Fish vitaplus, AQ grow-G, Oxy flow, Oxy max and O2-marine were most widely used compounds. Fourteen branded antibiotics were found in market of which Oxysentin, Renamox, Renamycin and Orgamycine were being widely used. Thirty three pharmaceutical companies were producing and marketing these products. The study also identified the problems associated with the use of chemicals which included lack of knowledge regarding use of chemicals, appropriate dose, method of application and indiscriminate use of chemicals. Keywords: Chemicals; Antibiotics; Aquaculture; Health management DOI: 10.3329/jbau.v6i2.4838 J. Bangladesh Agril. Univ. 6(2): 381-390, 2008